Vaginal and rectalmisoprostol for first trimester termination of pregnancy - Pant, PR; Sharma, J; Shrestha, R (Journal of Institute of Medicine Nepal, 2007)
Background: To compare the effectiveness of vaginal misoprostol with rectal misoprostol for termination of first trimester pregnancy. Prospective comparative study done on 138 women with unwanted pregnancy. Methods: This study was conducted in Vinayak hospital Kathmandu, from April 2005 to March 2006 (Baisakh 2062-Chaitra 2062) i.e. one year. Atotal of 138 women with unwanted pregnancy of 6- 12 weeks, and only those who agreed to participate were included in the study after written consent. Patients with scarred uterus following previous cesarean section, myomectomy or hysterotomy, known allergic to misoprostol, diarrhea, and fever, age below16 and above 45 were excluded from the study. Abortion was induced with 8oo?gmofmesoprostol in alternative patients vaginally in posterior fornix (group A) and per rectally (group B) Result: The age of the patients ranged from 16 -42 years and parity primi to sixth gravida. In group A54 patients out of 69( 78.2%) expelled products of conception after first dose of misoprostol within 24hours.15(21.7%) patients required repeat insertion of the drug .of these 8 expelled within the next 24 hours, whereas 7(10.1%) patients needed manual vacuum aspiration . In group B out of the 69 patients 59(85.5%) expelled product of conception within 24 hours of insertion of mesoprostol per rectally while the rest 10(14.4%) required re insertion of the drug. Out of these 10 cases 6 expelled within next 24 hours and four (5.8%) needed manual vacuum aspiration. Side effects of misoprostol: diarrhea, nausea, vomiting, headache and rigor were found to be more in rectal group than the vaginal. Conclusion: For termination of first trimester pregnancy, rectal route of mesoprostol is more effective than the vaginal route , how ever the side effects like diarrhea pyrexia, headache were more in rectal group. Key words: misoprostol, termination of pregnancy, unwanted pregnancy. The full text of this paper is available at Journal of Institute of Medicine website